A Food Systems Intervention in Rural Timor-Leste Increased Household Fish Purchases and Women’s Fish Consumption: Results From a Randomized, Controlled Trial - Byrd, Kendra; Tilley, Alexander; Dos Reis Lopes, Joctan; Longobardi, Lorenzo; Bonis-Profumo, Gianna; Klumpyan, Katherine; Shikuku, Kelvin (Oxford University Press, 2024)
Fish-aggregating devices (FADs) are simple devices commonly placed nearshore to attract fish and make them easier to catch. FADs help fishers adapt to climate change-related fishery declines and have been established as a tool to increase fish catch, but no study has evaluated whether this increase in catch makes its way into local households.